Policing Vulnerability: the Care and Control of Sex Workers Through Designated Police Officers - Brown, Kate (The British journal of criminology, 2025)
The state’s duty to protect vulnerable people gives rise to powerful forms of social intervention, especially in policing. This article reports from co-produced multimethods research focussed on one form of policing vulnerability within an English police force; the role of a specialist sex worker liaison officer (SWLO). Findings highlight that an enhanced focus on vulnerability through the role was highly valued by sex workers; building trust and improving investigations of crimes against sex workers. However, social control was the defining parameter for the intervention, with different implications across the diversity of the sex industry. Drawing on Gilson’s (2021) intersectional feminist philosophy work, we situate findings within critical attention to policing vulnerability, arguing the embedding of vulnerability within governance apparatus orientated to social control must be met with vigilance if it is to be progressive rather than reactionary.